The Effectiveness Of The Minimum Age Limit For Marriage In Addressing The Increase Of Child Marriages In Bogor District Based On Law Number 16 Of 2019 (Study At Cibinong Religious Court) - Buchori, Muhammad Azril; Ratnawaty, Latifah; Fajri, Ibrahim (JURNAL MAHASISWA YUSTISI, 2024)
The Effectiveness Of The Minimum Age Limit For Marriage In Addressing The Increase Of Child Marriages In Bogor District Based On Law Number 16 Of 2019 (A Study At Cibinong Religious Court), Muhammad Azril Buchori Npm: 201103010310.This research aims to evaluate the effectiveness of Law Number 16 of 2019 in addressing the increase of child marriages in Bogor District, considering the phenomenon of increased applications for marriage dispensation following the enactment of Law Number 16 of 2019. This study is a legal research employing an empirical normative approach. The method used is qualitative, with data collection through in-depth interviews with judges from Cibinong Religious Court and analysis of relevant documents.The research findings indicate that Law Number 16 of 2019 has not been effective in addressing the increase of child marriages in Bogor District. There has been a significant increase of 50% in the number of applications for dispensation of underage marriages at Cibinong Religious Court post-enactment of Law Number 16 of 2019. Internal factors contributing to this include proximity between couples, premarital pregnancy, and inadequate family supervision. External factors include narrow religious interpretations, low educational attainment, influence of technology and media, economic pressures, and diverse geographic conditions.